The Echoes of Danger from Tallinnn: The Reaction of the Lithuanian Armed Forces Command to the Communist Uprising in Tallinn on 1st of December in 1924 - Kilinskas, Kęstutis (Lietuvos istorijos studijos, 2020)
The article analyzes the reaction of the Lithuanian Armed Forces Command to the Communist putsch in Tallinn in 1924. News to the Lithuanian Armed Forces command about the communist uprising in Tallinn was reached through diplomatic channels, newspapers published in Lithuania and the Political Police. Following the events in Estonia, the Lithuanian Armed Forces Command realized the danger of a communist uprising in Lithuania and developed military plans to suppress a possible communist uprising. According to these plans, units of the Armed Forces and Lithuanian Riflemen’s Union had to protect the most important state objects (railway lines, highways, bridges, stations, state institutions, banks, prisons, postal, telephone and telegraph stations), ensure their functioning during the Communist uprising anywhere in Lithuania and we ready to fight Communist uprising. The entire territory of Lithuania, according to the borders of the Military Garissons, was divided into security areas, and arial commanders were appointed, in each area the most important objects of the state were identified and divisions of troops and rifles were assigned to protect them.
Keywords: Military forces; communists; uprising; revolt in Tallinn 1924; military planning and plans; Lithuanian Riflemen union; Secret police